Criminal Contribution to Unintentional Crimes: A Study Subject to the Provisions of Palestinian Legislation - Safadi, Diaa (Journal of Legal Studies and Researches, 2023)
The present study aims to show the original and consequential criminal contribution to unintentional crimes, and one of the most prominent results of the study is that it is agreed upon that the original criminal contribution to non-intentional crimes, while the difference in it is the consequential contribution to non-intentional crimes.